PROBLEMS OF INCREASING PROFESSIONAL COMPETENCE IN SHAPING MUSIC TEACHERS - Rasulova Saida Sabirovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article describes aspects of the compensatory approach of future music teachers in the process of preparation for pedagogical activity. In addition, the theoretical bases of increasing professional competence in the future music teachers and the competitions on music, which should be possessed by future teachers in the organization of activities of the science of music culture, were analyzed.